An Ever-Shadowed Past? Citizens’ Attitudes towards the Dictatorship in Twenty-First Century Portugal - Santana-Pereira, José (2016)
Several years after the transition to democracy, positive attitudes towards the authoritarian past are still observable in Portugal: the belief that the previous regime had more good things than bad things is expressed by about one-fifth  of the Portuguese. What explains this nostalgic sentiment? Are factors such as socialisation under the regime, party identification or religiosity more important than satisfaction with democracy and the state of the economy? The empirical analysis suggests that the relevance of these factors varies considerably, but socialisation phases lead to different stances on the past both in routine times and in times of economic crisis.